2016
DOI: 10.1097/olq.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Increased Gonorrhea Screening and Case Finding After Implementation of Expanded Screening Criteria—Urban Indian Health Service Facility in Phoenix, Arizona, 2011–2013

Abstract: After introduction of expanded gonorrhea screening, there was a significant increase in gonorrhea screening coverage and a subsequent increase in gonorrhea case finding among females. Despite increased screening in all clinics, increased case finding only occurred in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[8][9][10][11][12][14][15][16][17][18][19] Studies have shown, however, that EHR reminders alone have a limited positive effect on preventive care: in a review of 28 trials of EHR-based screening reminders, the median improvement rate for the measures evaluated was 4.2%. [14][15][16][17][18][19] "Alert fatigue"-induced by information overload-may limit the benefits of EHR reminder systems. Evaluations of alert fatigue and barriers to clinical decision support systems highlight the effect of these factors on health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][14][15][16][17][18][19] Studies have shown, however, that EHR reminders alone have a limited positive effect on preventive care: in a review of 28 trials of EHR-based screening reminders, the median improvement rate for the measures evaluated was 4.2%. [14][15][16][17][18][19] "Alert fatigue"-induced by information overload-may limit the benefits of EHR reminder systems. Evaluations of alert fatigue and barriers to clinical decision support systems highlight the effect of these factors on health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study draws on an unconventional and nuanced approach to sexual health self-care through the use of self-assessments combined with personalized messaging, and self-administered non-clinic based STI screening. These approaches have the potential for widespread uptake within communities served by Indian Health Service, and provide complementary alternatives to provider-driven, clinic-based care [4, 11, 13, 16]. Third, the self-assessment will include a risk prediction/clinical prediction rule to assist with identifying those at greatest risk for STIs, which is urgently needed in this and other settings where STI rates are climbing.…”
Section: Discussionmentioning
confidence: 99%
“…Further, because many STIs can be treated free of charge within the Indian Health Service (IHS), differential access to screening and treatment may explain these disparities [3]. Data from IHS corroborate inequalities in access to care, namely underutilization of services by higher risk groups and a lack of universal promotion of sexual health care by providers [4, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Six references described an outbreak response for syphilis 4 and gonorrhoea. 2 STI testing and treatment within the Indian Health System are primarily provided in outpatient clinics and emergency departments 37,[73][74][75][76][77][78][79][80][81] and are delivered according to national guidelines. 73 Expedited partner therapy (EPT) is available in some clinical settings.…”
Section: Clinical Service Deliverymentioning
confidence: 99%
“…83,84 Clinical decision support in electronic health records is utilised at many facilities as testing bundles or screening reminders for bacterial STIs and HIV with a single order set to enhance screening. [76][77][78][79] In some situations, such as outbreaks or in review of local epidemiology, STI screening and clinical decision support can be expanded based on local policy and practice needs. 77,80,81 In comparison to non-Hispanic Whites, AI/AN men and women have been reported to more likely seek STI services.…”
Section: Clinical Service Deliverymentioning
confidence: 99%